Principles of Sequence Stratigraphy - Catuneanu, Octavian, 1962- (Elsevier, 2022)
Principles of Sequence Stratigraphy, Second Edition presents principles to practical workflow that guide applications in a consistent manner that is independent of model, geological setting and the types and resolution of the data available. The book explains the points of agreement and difference between the various approaches to sequence stratigraphy, while also defining the common ground that affords the standard application of the method. This enables the practitioner to avoid nomenclatural and methodological confusions and apply sequence stratigraphy. The text is richly illustrated with hundreds of full-color diagrams and examples of outcrop, borehole and seismic data. The book's balanced approach helps students and professionals acquire a sound understanding of the concepts and methodology. It will appeal to geologists, geophysicists and engineers with interest in basin analysis, stratigraphy and sedimentology, as well as in all economic applications that concern the exploration and production of natural resources, including water, hydrocarbons, coal and sediment-hosted mineral deposits.